Armed Conflict as a Media Project of the 21st Century: Ukrainian Case - Gennady Kosov; Olga Yarmak; Olga Litvishko; Alexandr Gapich (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2023)
Introduction. Modern armed confrontation has an obligatory information component and, moreover, can be a kind of media project in a situation where the confrontation is based on a contradiction between military and political goals. Based on the results obtained, the authors concluded that new media are a mechanism for implementing a media project to transform “real” reality, change the media and supra-real (cognitive, mental, or reflective) realities. Methods and materials. During the study, over 1900 images and videos were analyzed posted in the network communities of social media VKontakte, Odnoklassniki, and Twitter, as well as the Telegram communication messenger, from February to May 2022. Analysis. Modern armed confrontation is a new type of social connection since the Internet, social media, and politics form new political and communicative ties in society, which, in turn, create or destroy political forces and change political regimes and economic players for markets. Result. The authors propose a model connecting physical, informational, and virtual spaces, explaining network communication creation and functioning. This model influences politics, economics, resources, and territories through people’s mass consciousness. Authors’ contribution. G.V. Kosov developed the theoretical basis of the study and carried out the general scientific editing of the article. O.V. Yarmak analyzed the dominant trends in modern media projects and the Ukrainian case. O.M. Litvishko interpreted the results of theoretical and empirical studies characterizing the process of forming a new media project. A.E. Gapich organized studies of images and videos posted in the network communities of social media (VKontakte, Odnoklassniki, Twitter), as well as the Telegram messenger.